To what extent does the CO2 diurnal cycle impact flux estimates derived from global and regional inversions? - S. Munassar; S. Munassar; S. Munassar; C. Rödenbeck; M. Gałkowski; M. Gałkowski; F.-T. Koch; F.-T. Koch; K. U. Totsche; K. U. Totsche; S. Botía; C. Gerbig (Atmospheric Chemistry and Physics)
Ignoring the diurnal cycle in surface-to-atmosphere CO2 fluxes leads to a systematic bias in CO2 mole fraction simulations sampled at daytime because the daily mean flux systematically misses the CO2 uptake during the daytime hours. In an atmospheric inversion using daytime-selected CO2 measurements at most continental sites and not resolving diurnal cycles in the flux, this leads to systematic biases in the estimates of the annual sources and sinks of atmospheric CO2. This study focuses on quantifying the impact of this diurnal cycle effect on the annual carbon fluxes estimated with the CarboScope (CS) atmospheric inversion at regional, continental, and global scales for the period of time 2010–2020. Our analysis is based on biogenic fluxes of hourly net ecosystem exchange (NEE) obtained from the data-driven FLUXCOM-X estimates, together with global and regional atmospheric transport models. Differences between CO2 mixing ratios simulated with daily averaged and hourly NEE from FLUXCOM-X range between around −2.5 and 7 ppm averaged annually throughout a site network across the world. These differences lead to systematic biases in CO2 flux estimates from the atmospheric inversions. Although the impact on the global total flux is negligible (around 2 % of the overall land flux of −1.79 Pg C yr−1), we find significant biases in the annual flux budgets at continental and regional scales. For Europe, the annual mean difference in the fluxes arising indirectly from the diurnal cycle of CO2 through the boundary condition amounts to around 48 % of the annual posterior fluxes (0.31 Pg C yr−1) estimated with CarboScope-Regional (CSR). Furthermore, the differences in NEE estimates calculated with CS increase the magnitude of the flux budgets for some regions such as North American temperate forests and northern Africa by a factor of about 1.5. To the extent that FLUXCOM-X diurnal cycles are realistic at all latitudes and for the station set including many continental stations as used in our inversions here, we conclude that ignoring the diurnal variations in the land CO2 flux leads to overestimation of both CO2 sources in the tropical lands and CO2 sinks in the temperate zones.